Homoepitaxial Growth of Large‐Scale Highly Organized Transition Metal Dichalcogenide Patterns. Issue 4 (8th December 2017) - Chen, Jianyi; Zhao, Xiaoxu; Grinblat, Gustavo; Chen, Zhongxin; Tan, Sherman J. R.; Fu, Wei; Ding, Zijing; Abdelwahab, Ibrahim; Li, Yi; Geng, Dechao; Liu, Yanpeng; Leng, Kai; et al.
Abstract: Controllable growth of highly crystalline transition metal dichalcogenide (TMD) patterns with regular morphology and unique edge structure is highly desired and important for fundamental research and potential applications. Here, single‐crystalline MoS2 flakes are reported with regular trigonal symmetric patterns that can be homoepitaxially grown on MoS2 monolayer via chemical vapor deposition. The highly organized MoS2 patterns are rhombohedral (3R)‐stacked with the underlying MoS2 monolayer, and their boundaries are predominantly terminated by zigzag Mo edge structure. The epitaxial MoS2 crystals can be tailored from compact triangles to fractal flakes, and the pattern formation can be explained by the anisotropic growth rates of the S and Mo edges under low sulfur chemical potential. The 3R‐stacked MoS2 pattern demonstrates strong second and third‐harmonic‐generation signals, which exceed those reported for monolayer MoS2 by a factor of 6 and 4, correspondingly. This homoepitaxial growth approach for making highly organized TMD patterns is also demonstrated for WS2 . Abstract : Homoepitaxial growth of highly organized transition metal dichalcogenide patterns is realized via chemical vapor deposition. The regular MoS2 dendritic patterns are rhombohedral (3R)‐stacked with the underlying monolayer and possess a unique zigzag Mo edge structure. The highly organized MoS2 pattern/monolayer hybrid heterostructure promises important applications in nonlinear optics and catalysis. This growth approach is also demonstrated for WS2 patterns.